Naïve and Innate Memory phenotype CD4(+) T-cells have different requirements for active Itk for their development - Hu, Jianfang (2008)
The Tec family kinase Itk regulates the development of conventional and innate CD8(+) T cells, however little is known about the role of Itk in the development of CD4(+) T cell lineages, although the role of Itk in the T cell activation and function is well defined. We show here that the Itk null mice have increased percentage of CD62L(Lo)CD44(Hi) memory phenotype CD4(+) T cells compared to WT mice. These cells arise directly in the thymus, express high levels of transcripts for the T-bet and IFNγ and are able to produce IFNγ directly ex vivo in response to stimulation. Itk deficiency greatly decreases the number of CD4(+) T cells with CD62L(Hi)CD44(Lo) naïve phenotype, but has no effect on the number of memory phenotype CD4(+) T cells, indicating that the development of memory phenotype CD4(+) T cells is Itk independent. We further show that the development of the naïve phenotype CD4(+) T cells is dependent on active Itk kinase signals and can be rescued by expression of Itk specifically in T cells. Our data also show that the Itk is required for functional TCR signaling in these cells, but not for the innate function in response to IL-12/IL-18 or L. monocytogenes stimulation. These results indicate that CD62L(Hi)CD44(Lo) “naïve” and CD62L(Lo)CD44(Hi) “innate memory phenotype” CD4(+) T cells may be independent populations that differ in their requirement for Itk’s signals for development. Our data also suggest that CD4(+)CD62L(Lo)CD44(Hi) memory phenotype T cells have innate immune function.